Physiological Markers of Motor Inhibition during Human Behavior. Issue 4 (April 2017) - Duque, Julie; Greenhouse, Ian; Labruna, Ludovica; Ivry, Richard B.
Abstract : Transcranial magnetic stimulation (TMS) studies in humans have shown that many behaviors engage processes that suppress excitability within the corticospinal tract. Inhibition of the motor output pathway has been extensively studied in the context of action stopping, where a planned movement needs to be abruptly aborted. Recent TMS work has also revealed markers of motor inhibition during the preparation of movement. Here, we review the evidence for motor inhibition during action stopping and action preparation, focusing on studies that have used TMS to monitor changes in the excitability of the corticospinal pathway. We discuss how these physiological results have motivated theoretical models of how the brain selects actions, regulates movement initiation and execution, and switches from one state to another. Trends: Many aspects of behavior result in inhibition of the corticospinal motor output pathway. The state of excitability of the corticospinal pathway can be assessed with single-pulse transcranial magnetic stimulation (TMS) over primary motor cortex (M1). The pulse elicits a temporally precise motor evoked potential (MEP) in the electromyography (EMG) recording from the targeted muscle. To measure the dynamics of excitability, MEPs are measured at various stages of task performance and compared in amplitude with MEPs measured at baseline (e.g., during the intertrial interval). Inhibition is evident when the MEPs are lower relative to baseline. Motor inhibition is found when an ongoing or planned action needs to be aborted following a stop signal (reactive inhibition). In this context, behavioral inhibition is associated with a fast and global decrease in corticospinal excitability. This reactive inhibition is thought to rely on corticobasal ganglia loops via hyperdirect projections from the frontal cortex to the subthalamic nucleus (STN), providing a mechanism to generically brake the motor output. Inhibition of the motor system is also evident in anticipation of a stop signal. Proactive inhibition has been characterized using selective stop tasks, where only part of an ongoing action needs to be interrupted. In this context, inhibition operates in a more focal manner, raising the hypothesis that separate basal ganglia pathways are recruited during behavioral inhibition, exerting broad or focal inhibitory influences depending on task demands. Several markers of motor inhibition can be observed during the period preceding a voluntary movement (preparatory inhibition). These markers are modulated by various task variables, suggesting a role for inhibition in response selection and response initiation. The functional role of preparatory inhibition has been the subject of considerable debate. One hypothesis is that preparatory inhibition serves to assist action selection through a competitive process, whereby excitation of selected action representations is associated with the suppression of unwanted (inappropriate) action representations. Another hypothesis has focused on the regulation of response initiation, with inhibition serving to prevent premature movement, while preparatory activity unfolds across the cortex. A third view is that preparatory inhibition may serve to modulate the gain of the motor system. A reduction in background motor activity could facilitate movement onset by increasing the signal:noise ratio. This last hypothesis shifts the emphasis away from inhibition as a way to suppress unwanted or nonselected movements, to one in which preparatory inhibition promotes rapid action selection and implementation. The relationship in terms of psychological function and neural mechanisms between reactive, proactive, and preparatory inhibition is an important challenge for future research.